Digital technologies to assess and mitigate the abiotic stress in horticultural crops - Morade, Amrut S.; Khapte, Pratapsingh S.; Changan, Sushil S.; Kakade, Vijaysinha D.; Chavan, Sangram B.; Reddy, K. Sammi (Indian Horticulture, 2025)
The Indian horticulture industry plays a crucial role in ensuring national food and nutritional security, yet it faces significant challenges from abiotic stressors, including drought, salinity, extreme temperatures, and irregular rainfall, which are exacerbated by climate change. These stress factors negatively affect crop yield and quality, threatening farmers' livelihoods. To mitigate these effects, digital technologies such as remote sensing, the Internet of Things (IoT), machine learning, and drones offer innovative solutions. These technologies enable realtime monitoring, early detection, and targeted interventions to reduce stress and improve crop resilience. Remote sensing and GIS aid in monitoring and managing stress by analyzing environmental factors and crop conditions, while IoT systems optimize irrigation through precise adjustments based on real-time data. Drones equipped with advanced sensors help detect stress and apply interventions like nutrient delivery and water management, particularly in diverse agro-climatic zones. Despite their potential, the adoption of these technologies faces barriers such as high costs, lack of skilled operators, and regulatory challenges. To scale up these innovations, government support and training are crucial. High-throughput phenotyping and imaging technologies further enhance stress management by providing valuable insights into crop health and development. Overall, digital tools are transforming the Indian horticulture landscape, offering significant potential to enhance productivity, sustainability, and resilience against abiotic stresses.